Developing the hypoglycemia-nursing early warning score system (Hy-NEWSS): A pilot study - Ahmad Hasyim Wibisono; Dennti Kurniasih; Eti Sumartiyah; Rima Novia Putri; Dikha Ayu Kurnia; Yunisar Gultom; Debie Dahlia (SAGE Publishing, 2021)
Background: Severe hypoglycemia occurs in 6% of type 2 DM patients with a 6 to 7% mortality rate. Amidst the COVID-19 pandemic, there has been a higher rate of fatality among diabetes patients, at least 22% of COVID-19 deaths in Wuhan, China. Furthermore, the condition impairs physiological defense against recurrent hypoglycemia in the future. Accordingly, the innovation in this study aims to prevent severe hypoglycemia among type 2 patients through early risk screening, the use of preventative protocols, and patient and family empowerment. This intervention bundle is called Hypoglycemia-Nursing Early Warning Score System (Hy-NEWSS). Design and Methods: The innovation was implemented in inpatient and outpatient settings, within two weeks with the following sequence: i) internal training, ii) Hy-NEWSS implementation, iii) outcomes evaluation. Results: Of the twenty-eight patients involved in the study, 3 patients (19%) had a high risk of hypoglycemia, while the remaining had a low risk for the condition. However, at the end of the study there was no event of severe hypoglycemia (0%), and only 1 event (6.33%) of mild hypoglycemia. The results also showed that the accuracy of nurses in implementing the protocols was 93% and that during the evaluation, 95.62% of the responses of the nurses from the inpatient and outpatient settings were positive. Finally, the scores of the sensitivity and specificity evaluation were 99% and 88%, respectively. Conclusion: It may be concluded from this initial study that Hy-NEWSS is effective in preventing severe hypoglycemia, accurate in identifying patient risk level for the condition, and has high applicability to be implemented in hospital settings.